The Penny Mansions - Mayfield, Steven ([Place of publication not identified] : Regal House Publishing, 2023)
With the Spanish flu pandemic on the rise, a former gold rush town-- once the largest city in the Pacific Northwest-- is threatened with extinction via eminent domain should their population fall below 125 citizens. To save their homes, former madam Maude Dollarhyde, her mixed-race grand-daughter, Bountiful, and their fellow council members agree to sell four abandoned mansions for a penny apiece if the buyers will stay in town long enough to be counted in the 1920 census. Soon, an eclectic cast of newcomers arrives, including a New York actor and his questionably-familial family; a lawyer with an agoraphobic wife, mute son, and austere nanny; six excommunicated Mormons; and the great-nephew of the town's hated former boss. As real estate developer and politician Gerald Dredd plots to foil the council's plan, the new families move in and knock over the first domino in a row that includes three romances, twelve sticks of dynamite, an unintentionally hilarious community theater production, an investigation by a Chicago insurance detective, and last of all, murder!
New Book 2023.
Keywords: Murder; Detective and mystery stories; West (U.S.)